Genetically inspired in vitro reconstitution of Saccharomyces cerevisiae actin cables from seven purified proteins - Pollard, Luther W. (Mol Biol Cell, 2020)
A major goal of synthetic biology is to define the minimal cellular machinery required to assemble a biological structure in its simplest form. Here, we focused on Saccharomyces cerevisiae actin cables, which provide polarized tracks for intracellular transport and maintain defined lengths while continuously undergoing rapid assembly and turnover. Guided by the genetic requirements for proper cable assembly and dynamics, we show that seven evolutionarily conserved S. cerevisiae proteins (actin, formin, profilin, tropomyosin, capping protein, cofilin, and AIP1) are sufficient to reconstitute the formation of cables that undergo polarized turnover and maintain steady-state lengths similar to actin cables in vivo. Further, the removal of individual proteins from this simple in vitro reconstitution system leads to cable defects that closely approximate in vivo cable phenotypes caused by disrupting the corresponding genes. Thus, a limited set of molecular components is capable of self-organizing into dynamic, micron-scale actin structures with features similar to cables in living cells.